Timing of Therapeutic Extractions Can Affect En Masse Anterior Retraction: A Split Mouth Randomized Clinical Trial - Devi Priya; Shobha Sundareswaran; Navnita Mishra; SreehariSathyanathan; Mohammed Shibin; Baby Jisha (Turkish Journal of Orthodontics)
Objective: To investigate the effect of deferred timing of therapeutic extraction on the rate of space closure during en masse anterior retraction. Methods: Twenty-six patients (aged 16-24 years) with bimaxillary protrusion, crowding <3 mm, requiring bilateral extraction of four first premolars were recruited. Permuted block randomization was done. Allocations were concealed in opaque envelopes which were numbered and sealed. Each patient’s right and left quadrant was randomly assigned for premolar extraction. The extraction of the contralateral side was deferred until the commencement of retraction. The primary outcome was the rate of space closure, and the secondary outcomes were anchorage loss and canine rotation. Blinding was applied only during the outcome assessment. The independent t-test and Intraclass correlation tests were used for statistical evaluation. Results: Twenty-four patients completed the study. The mean rate of space closure over a period of 4 months was found to be significantly higher for the recently extracted site (0.818±0.208) when compared with healed site(0.426±0.184)(p<0.001). The tipping of the canine was also significantly higher for the former (6.042°±1.398°) than the latter (5.125°±1.035°) (p<0.05). However, the amounts of anchorage loss and canine rotation were insignificant. No adverse effects were noted. Conclusion: The rate of space closure at the recent extraction site was faster than that at the healed site. There was no significant difference in the mesial movement of anchorage molars or rotation of canines into the extraction site. The tipping of canines was significantly greater in the recent extracted quadrant. The results of this trial indicate a clinical recommendation to initiate orthodontic retraction immediately following therapeutic extractions and offer a practical, non-invasive, safe procedure for increasing the rate of tooth movement.